2006
DOI: 10.1097/01.md.0000232560.22098.4e
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infections in Adults With Hematologic Malignancies and Human Stem Cell Transplantation Recipients

Abstract: Community respiratory viruses (CRVs) have been recognized as a potential cause of pneumonia and death among hematopoietic stem cell transplantation (HSCT) recipients and patients with hematologic malignancies. We reviewed the Microbiology Laboratory records dated from July 1, 2000, to June 30, 2002, to identify patients who had respiratory specimens positive for influenza, parainfluenza, respiratory syncytial virus, or picornavirus. We identified 343 infections among patients with underlying hematologic malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
311
8
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(342 citation statements)
references
References 49 publications
16
311
8
7
Order By: Relevance
“…This is consistent with our observation that hypogammaglobulinemia was associated with fatal outcome. Other risk factors, such as age 33 or RSV infection pre-engraftment, 32,34,35 were not statistically significant in our univariate or multivariate analysis. We also did not find any significant difference in median time to RSV infections in hematology and transplant unit N Lehners et al leukocyte recovery in patients infected before versus after engraftment, as found by others.…”
Section: Rsv Infections In Hematology and Transplant Unit N Lehners Ementioning
confidence: 75%
“…This is consistent with our observation that hypogammaglobulinemia was associated with fatal outcome. Other risk factors, such as age 33 or RSV infection pre-engraftment, 32,34,35 were not statistically significant in our univariate or multivariate analysis. We also did not find any significant difference in median time to RSV infections in hematology and transplant unit N Lehners et al leukocyte recovery in patients infected before versus after engraftment, as found by others.…”
Section: Rsv Infections In Hematology and Transplant Unit N Lehners Ementioning
confidence: 75%
“…4 It is said that their treatment with cytotoxic chemotherapy drugs induced a reduction of humoral response and led to increased susceptibility to infectious disease. [5][6][7] In fact, high mortality and morbidity of this population due to an influenza virus was reported. 8 On the other hand, it is unclear whether the underlying disease causes this lowered response.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, LRTI, prolonged viral shedding, hospitalization, longer antiviral treatment, ventilator requirement and H1N1 resistance were documented only in SID patients. Lymphopenia, which has been previously reported as a risk factor for LRTI, both for community-acquired RVI [1][2][3][4]33 and for H1N1 influenza 9,[14][15][16][17][18]26 was observed in six patients at the time of diagnosis. Chronic GvHD and its corollary of long-term immunosuppression has also been associated with the risk of developing RVI and LRTI.…”
Section: Discussionmentioning
confidence: 99%